Factors influencing transfection efficiency of pIDUA/nanoemulsion complexes in a mucopolysaccharidosis type I murine model - Fraga M (Dove Medical Press, 2017)
Michelle Fraga,1,2 Talita Giacomet de Carvalho,2,3 Juliana Bidone,1 Roselena Silvestri Schuh,1,2 Ursula Matte,2,3 Helder Ferreira Teixeira1 1Pharmaceutical Sciences Graduate Program, Universidade Federal do Rio Grande do Sul, 2Gene Therapy Center, Experimental Research Center, Hospital de Clínicas de Porto Alegre, 3Genetics and Molecular Biology Graduate Program, Universidade Federal do Rio Grande do Sul, Porto Alegre, Brazil Abstract: Mucopolysaccharidosis type I (MPS I) is an autosomal disease caused by alpha-L-iduronidase (IDUA) deficiency. This study used IDUA knockout mice as a model to evaluate whether parameters such as dose of plasmid and time of treatment could influence the transfection efficiency of complexes formed with PEGylated cationic nanoemulsions and plasmid (pIDUA), which contains the gene that encodes for IDUA. Formulations were composed of medium chain triglycerides, 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-(amino[polyethylene glycol]-2000), 1,2-dioleoyl-sn-glycero-3-trimethylammonium propane (DOTAP), glycerol, and water and were prepared by the adsorption or encapsulation of preformed pIDUA–DOTAP complexes by high-pressure homogenization. A progressive increase in IDUA expression was observed with an increase in the dose and time of transfection for mice treated with both complexes (adsorbed and encapsulated), especially in the liver. Regardless of the complex administered, a significant increase in IDUA activity was detected in lungs and liver compared with nontreated MPS I when a dose of 60 µg was administered and IDUA activity was measured 7 days postadministration. Tissue sections of major organs showed no presence of cell necrosis, inflammatory infiltrate, or an increase in apoptosis. Furthermore, immunohistochemistry for CD68 showed no difference in the number of macrophage cells in treated and nontreated animals, indicating the absence of inflammatory reaction caused by the treatment. The data set obtained in this study allowed establishing that factors such as dose and time can influence transfection efficiency in different degrees and that these complexes did not lead to any lethal effect in the MPS I murine model used. Keywords: cationic nanoemulsions, DSPE-PEG, MPS I, plasmid, pIDUA